2003
DOI: 10.1067/mtc.2003.54
|View full text |Cite
|
Sign up to set email alerts
|

Importance of preserving the apex and plication of the base in left ventricular volume reduction surgery

Abstract: Apex-sparing volume reduction surgery capable of maintaining left ventricular fiber continuity provided better left ventricular function in both the systolic and diastolic phases than apex-sacrificing volume reduction surgery in the acute heart failure model. This modification might improve the results of left ventricular volume reduction surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…When an LV lesion is detected before operation and it is located at the posterolateral wall, as seen in muscular dystrophy, 68 the PLV seems to be an effective procedure for nonischemic DCM. 69,70 The operative results improved with the selection of the procedures, with elective operation, and mitral plasty for less cardiac dilatation. 71 The mid-term results of clinical status and LV function showed the effectiveness of the operation.…”
Section: Site Selection For Svrmentioning
confidence: 96%
“…When an LV lesion is detected before operation and it is located at the posterolateral wall, as seen in muscular dystrophy, 68 the PLV seems to be an effective procedure for nonischemic DCM. 69,70 The operative results improved with the selection of the procedures, with elective operation, and mitral plasty for less cardiac dilatation. 71 The mid-term results of clinical status and LV function showed the effectiveness of the operation.…”
Section: Site Selection For Svrmentioning
confidence: 96%
“…Although initial reports on the Batista procedure lacked significant information on its safety and effectiveness, the overall clinical impression was that the operation may serve as a bridge to HT especially in patients with idiopathic dilated cardiomyopathy. Komeda and Koyama reported animal studies that confirmed that apical sparing volume reduction surgery improved the outcome [3]. With good initial results published (Cleveland, Bristol, Japan, Sao Paulo, Belgrade) [4][5][6][7][8], clinicians were enthusiastic about the potential benefits of this surgery returning patients to a normal lifestyle without the long-term complications and cost related to immunosuppression and HT, and even more centers started the program.…”
Section: Introductionmentioning
confidence: 94%
“…Therefore, we need to downsize those dilated ventricles appropriately. Because we found a nonhomogeneous severity of interstitial fibrosis between the left ventricular free wall and the septum in idiopathic dilated cardiomyopathy [10,11], we introduced surgical exclusion site selection for the left ventriculoplasty procedure, which is the septal anterior ventricular exclusion (SAVE) [12] for bad septum cases and the modified partial left ventriculectomy (PLV) [13] when the lateral wall is the weakest part.…”
Section: Introductionmentioning
confidence: 99%